UPGRADING SMES EMPLOYEE PERFORMANCE WITH KNOWLEDGE SHARING AND INNOVATIVES BEHAVIOUR - Indah Rizky Ariani (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Indonesia's micro, small, and medium enterprises (MSMEs) continue to encounter a range of obstacles, particularly in enhancing their productivity and competitiveness. The 2020 survey conducted by the Ministry of Education and Cultural Affairs indicates that Indonesia still has substantial challenges in terms of education quality, especially in rural and underdeveloped urban areas. Several factors, such as the availability of high-quality education, access to educational resources, and the level of teaching excellence, can significantly impact individuals' capacity to effectively manage their enterprises and promote innovation (Kemendikbud RI, 2020). This study investigates the link between knowledge sharing practices, innovation, and employee performance within Indonesian MSMEs. Through exploratory analysis, it offers fresh insights into how innovation and knowledge sharing behaviour can affect employee performance in Indonesian MSMEs. The main objective is to analyse and explore the impact of innovation and information sharing behaviours on employee performance in small and medium-sized enterprises (SMEs) in Indonesia. Based on this research and its findings, several strategies have been identified. These strategies aim to explore the complex relationship between an employee's performance, their willingness to share knowledge, and their ability to demonstrate innovative behaviours in MSMEs. Future study could focus on improving the quality of human resources, specifically in areas such as knowledge, expertise, competence, and entrepreneurial attitude. Investing in the development of human resources yields benefits for both MSME business owners and the overall well-being of workers..